Comparative evaluation of platelet-rich fibrin versus connective tissue grafting in treatment of gingival recession using pouch and tunnel technique: A randomized clinical study - Vatsala Chandra; Vivek Kumar Bains; Rajesh Jhingran; Ruchi Srivastava; Rohit Madan (Wolters Kluwer Medknow Publications, 2022)
Aims: The aim of the study was to compare the clinical efficacy of platelet-rich fibrin (PRF) and connective tissue grafting in the treatment of gingival recession (GR) using pouch and tunnel (P and T) technique. Materials and Methods: A total of 40 Class I or Class II GR defects in 17 patients were randomized treated with P and T with PRF (Group I, n = 20) and P and T with CTG (Group II, n = 20). The parameters measured were plaque index (PI), gingival index (GI), probing pocket depth (PPD), clinical attachment level (CAL), horizontal gingival recession (HGR), vertical gingival recession (VGR), width of attached gingiva (WAG), width of keratinised gingiva (WKG), gingival thickness-mid buccal (GTMB), and gingival thickness interdental papilla (GTIP). Postsurgical discomfort level (PSDL), hypersensitivity score (HS), and patient esthetic score (PES) were recorded using visual analog scale (VAS). The PI, GI, PPD, CAL, HGR, VGR, WAG, WKG, GTMB, and GTIP were assessed at pretreatment (baseline) and 1-, 3-, and 6-month posttreatment. The PSDL, HS, and PES were assessed at baseline, day 10, 1, 3, and 6-month posttreatment. Results: P and T with PRF and CTG resulted in root coverage of 73.75% ± 7.80% and 70.83% ±8.26%, respectively. Patient response and acceptance for the surgical treatment modality showed less discomfort and better esthetics in Group I as compared to Group II. Conclusions: PRF treated sites were comparable to the gold standard CTG with better patient acceptance and a lesser invasive approach in terms of graft procurement.